Literacy for life: The use of affective mediation rubric and guidelines to develop educational TV programmes - Abdul Rahim, Fauziah; Husni, Husniza; Abdul Salam, Sobihatun Nur; Shaik Abdullah, Sarimah; Kanagasabai, Suras (2014)
Inspired to increase Bahagian Teknologi Pendidikan (BTP) educational-web TV programmes in promoting literacy for life, this project combines expertise from education, computing and multimedia to help promote fun learning lessons and learning tools that place affective mediation as core.The overall objectives of the project are divided into two parts: firstly, to provide guidelines and rubrics on designing and developing resources for BTP and secondly, to produce samples of lessons and learning tools based on affective mediation.To achieve the first objective, two trainings on the guidelines and rubrics were provided to significant personnel in BTP that are directly involved in the production of BTP programmes.An initial training was done at BTP during the first year of the project and a second training (sustainable training) were done in the final year as a form of getting feedback from the community on the use of rubrics and guidelines.The first training was conducted by the interns whilst the second training was done in a team effort among academia and interns.The trainings enabled the BTP officers to become aware of the significance of their role in promoting and producing samples of good teaching and meaningful learning. The second objective was achieved through the analysis made on 8 lessons produced by BTP. It was found that all the lessons produced by BTP adhered to most of the guidelines and rubrics and coincidentally were deemed as lessons that exemplify best practices of literacy (Malay, English Language and Mathematics) lessons from rural, urban, affluent as well as disadvantaged contexts. The tangible outcomes of this project yielded three trajectories: the community (BTP), the society (teachers and students) and the academia. Positive changes not only can be derived directly from BTP officers through their reflection as a result of the training especially with one (the last author) enrolling to pursue a postgraduate study but also from some of the teachers who were involved as well as pupils’ performances which yielded a ripple effect of the project.As for the academia, developing a technological tool as part of the project for a disadvantaged suburban school to promote English literacy, also won recognition during an international exhibition.